Studi Kasus Integrasi Current Transformer (CT) dan EOCR untuk Pengamanan Arus pada Panel Cooling Tower Pump di PT DongJin Indonesia - Muhammad Dicky Saputra; Mohammad Fatkurrokhman (Jurnal Kendali Teknik dan Sains, 2026)
Three-phase induction motors are essential components in industrial cooling systems that require reliable overcurrent protection to maintain operational continuity and prevent equipment damage. In the Cooling Tower Pump panel at PT DongJin Indonesia, a limitation was identified where the terminal of the Electronic Overcurrent Relay (EOCR) could not accommodate the 50 mm² power cable, preventing direct current measurement. This study aims to analyze the effectiveness of integrating a 200:5 A Current Transformer (CT) with the EOCR as an adaptive protection solution that is both safe and efficient. The research employs a case study approach through field observation, motor current measurement using a Fluke 303 Clamp Meter, and descriptive analysis of the recorded data. The results indicate that the three motors operate under stable load conditions, with current values ranging from 236.7 A to 275.7 A, while the secondary current detected by the EOCR ranges from 3.7 A to 3.9 A, consistent with the CT transformation ratio. During the starting phase, the current surged to 600.4 A without causing false tripping, demonstrating that the EOCR effectively distinguishes temporary inrush current from actual fault conditions. Therefore, the integration of CT–EOCR is proven to enhance measurement safety, maintain motor operational stability, and support efficient system maintenance in industrial environments.